1996
DOI: 10.1111/j.1440-1746.1996.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to M2 mitochondrial autoantigens in normal human sera by immunofluorescence and novel assays

Abstract: Primary biliary cirrhosis (PBC) is characterized by the presence of antimitochondrial antibodies (anti-M2), directed against the E2 subunits of the 2-oxo-acid dehydrogenase complexes (2-OADC), chiefly pyruvate dehydrogenase complex (PDC-E2). We present here a detailed study, based on a large panel of normal sera, of the specificity of tests for anti-M2 by immunofluorescence and for anti-PDC by other assays for the diagnosis of PBC. The assays for anti-PDC included immunoblotting with bovine heart mitochondria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…(17)(18)(19) Systematic screening of blood donors and healthy subjects shows AMA-positive results in 0.07%-9.9% of individuals, depending on the techniques and diagnostic thresholds used, as well as on the type, age, and sex structures of the populations screened. (20)(21)(22)(23)(24) The relatively high rate (2.5% of all tests) of AMA positivity observed in our study may be related to the equivocal nature of low titers of AMAs detected by IF, but is more likely to be driven by the population concerned. The proportion of positive results is typically bigger in the female population above 40 years.…”
Section: Discussionmentioning
confidence: 72%
“…(17)(18)(19) Systematic screening of blood donors and healthy subjects shows AMA-positive results in 0.07%-9.9% of individuals, depending on the techniques and diagnostic thresholds used, as well as on the type, age, and sex structures of the populations screened. (20)(21)(22)(23)(24) The relatively high rate (2.5% of all tests) of AMA positivity observed in our study may be related to the equivocal nature of low titers of AMAs detected by IF, but is more likely to be driven by the population concerned. The proportion of positive results is typically bigger in the female population above 40 years.…”
Section: Discussionmentioning
confidence: 72%
“…We believe that our sample does not represent a true general population, but it is closer to a general population than those examined in previous studies. [17][18][19][20] Mattalia et al 17 and Turchany et al 18 reported that most AMA-positive persons had normal liver function. Mattalia et al 17 detected AMA in 9 (0.5%) in a sample of 1530; all AMA-positive persons had normal liver function.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Some of these previ- ous studies used an unacceptably large number of blood donors as study subjects, 17,19 or female-dominant samples, 17,19,20 or did not describe the age distribution, 17,19 or the sex ratio of the sample. 19 Blood donors have a self-selection bias, with subjects tending to be younger and healthier. One study selected a too-young sample, with a mean age of 31.7-years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] These studies raised the important question of whether AMA-positive healthy individuals would eventually develop PBC.…”
mentioning
confidence: 99%